Hubungan Gerakan Berulang Dengan Risiko Low Back Pain Di PT X Bekasi Tahun 2023 - Septian, Ipan; Sarwili, Indri; Agustina, Marisca (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Musculoskeletal conditions rank second as the largest cause of global disability, with low back pain being the leading cause of global disability. Low back pain is a symptom of discomfort or pain in the lower back area caused by disorders or abnormalities in the muscles and tendons without neurological involvement. If low back pain persists without efforts to address this health issue, it is feared that it may affect workers' performance, potentially leading to dismissal from the company or early retirement. This study aims to determine how repetitive movements contribute to the risk of low back pain. The research design is quantitative, adopting a descriptive correlational methodology with a cross-sectional approach. The population comprises all employees of PT. X, totaling 116 employees, with a purposive sampling technique using 53 respondents. The results show that the distribution of repetitive movements in the high category was 39.7%, and the high risk of low back pain was 43.4%. The Spearman Rank correlation coefficient was 0.783, indicating a very strong relationship since the r-value is close to 1, and the significance value (sig) was 0.000. Therefore, this study indicates that there is a relationship between repetitive movements and the risk of low back pain at PT. X.